2008
DOI: 10.1002/jnr.21821
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine protects cerebellar granule neurons from apoptotic cell death

Abstract: Cultured cerebellar granule neurons (CGNs) undergo apoptosis when deprived of depolarizing stimulation and provide an in vitro model system with which to study the effects of neurotrophic substances. Our previous results showed that secretory phospholipases A(2) (sPLA(2)s) protect CGNs from apoptotic cell death under the nondepolarizing condition. In this study, we further analyzed the mechanism whereby sPLA(2) exhibits this effect. Among the primary metabolites of sPLA(2) tested, lysophosphatidylcholine (LPC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
(57 reference statements)
2
11
0
Order By: Relevance
“…Interestingly, similar headgroup specificity of these lysophospholipids was observed in our previous studies wherein neurite outgrowth in PC12 cells and the cell survival of CGNs were examined; only LPC, but not other lysophospholipids, induced neurites in PC12 and rescued CGNs from apoptosis [20,21]. Furthermore, LPC with fatty acyl chains of C14:0, C16:0, C18:0, and C18:1, but not C12:0, enhanced NGF‐induced MAPK phosphorylation in this study, and similar LPC species were effective on neurite outgrowth in PC12 cells and the cell survival of CGNs in our previous studies [20,21]. These results suggest the existence of specific and acyl chain‐dependent role(s) of LPC in neuronal systems.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Interestingly, similar headgroup specificity of these lysophospholipids was observed in our previous studies wherein neurite outgrowth in PC12 cells and the cell survival of CGNs were examined; only LPC, but not other lysophospholipids, induced neurites in PC12 and rescued CGNs from apoptosis [20,21]. Furthermore, LPC with fatty acyl chains of C14:0, C16:0, C18:0, and C18:1, but not C12:0, enhanced NGF‐induced MAPK phosphorylation in this study, and similar LPC species were effective on neurite outgrowth in PC12 cells and the cell survival of CGNs in our previous studies [20,21]. These results suggest the existence of specific and acyl chain‐dependent role(s) of LPC in neuronal systems.…”
Section: Discussionsupporting
confidence: 56%
“…We previously demonstrated that sPLA 2 displays neurotrophin‐like activities, such as neurite‐induction in PC12 cells and rescue of CGNs from apoptosis. These effects of sPLA 2 were essentially attributable to the generation of LPC [20,21]. Here we tested if exogenously‐added sPLA 2 also enhances NGF‐induced MAPK phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous in vitro studies have demonstrated proapoptotic effect of LPC in human endothelial cells, hippocampal progenitor cells, and pancreatic exocrine cells . In contrast, exogenous treatment of LPC reduced low potassium‐induced apoptosis in cerebellar granule neurons in vitro . Taken together, LPC might play distinct roles specifically to tissues or cells.…”
Section: Introductionmentioning
confidence: 82%
“…9,10) We have reported that LPC significantly enhanced NGFinduced MAPK and Akt phosphorylation by stimulating the activation of TrkA in PC12 and CHO-K1 cells through the extracellular domain of TrkA. 11) In the present study, we aimed to determine whether LPC has a similar effect on the BDNF-TrkB pathway.…”
mentioning
confidence: 90%